Optical generation of acoustic waves - MLECZKO, Andrzej; BUKOWSKI, Roman; KLESZCZEWSKI, Zygmunt (Archives of Acoustics, 1983)
This paper discusses optical generation of acoustic waves and gives preliminary results of experimental research. The acoustic wave was generated as a result of the interaction of two laser light beams of very high intensity and slightly different frequencies. The change in the frequency of the laser beams (ΔF = 116 MHz) was achieved using the Bragg diffraction of laser light by the acoustic wave.